Precipitation and Mechanical Property of V‐Alloyed Steel: Role of Cooling Rate. Issue 2 (3rd December 2019) - Huang, Zhang; Yu, Hao; Song, Chenghao; Li, Shuying; Duan, Xiaoni; Wu, Weijia
Abstract : Herein, the effect of cooling rate on the precipitation behavior and mechanical properties of V‐added microalloyed steel is systematically investigated by nanoindentation test, X‐ray diffraction, and transmission electron microscopy. The present observation reveals that random precipitates and interphase precipitates are simultaneously observed at the low cooling rate of 0.5 °C s −1, whereas only random precipitates are obtained at the high cooling rate of 2 °C s −1 . The contribution of the nanoscale precipitates to yield strength is evaluated to be 199 MPa at the low cooling rate of 0.5 °C s −1, which is almost 4 times higher than that of 2 °C s −1 . The predicted yield strength by semiempirical model based on the structural parameters is consistent with the result from tensile testing. In addition, the greater difference between upper and lower yield points in sample B is caused by dislocations motion, which is related to the smaller interparticle spacing of nanosized precipitates within ferrite matrix. Abstract : The effect of cooling rate on the precipitation behavior and mechanical properties of V‐added microalloyed steel is systematically investigated in this study. The interphase precipitates and random precipitates are simultaneously observed in the ferrite matrix at the low cooling rate, which is essential for improving mechanical properties of microallyed steels.